Prototipo de electrocardiógrafo de 4 derivaciones bipolares con ingreso de datos por conexión bluetooth con diseño amigable para pacientes pediátricos - Espinoza López, Mariela Lizbeth (2025)
This study focuses on the development of a prototype electrocardiograph with an ergonomic and user-friendly design, specifically aimed at paediatric patients. The objective is to make the cardiac monitoring experience less intimidating and more accessible for children. The device incorporates a data input system using Bluetooth connectivity, designed to enable fast and efficient data entry. During the prototype validation process, clinical trials were conducted on paediatric patients under the supervision of a specialized cardiologist. These trials considered relevant psychological factors, such as the levels of stress and anxiety patients may experience during cardiac monitoring procedures. The effectiveness of the design was assessed in terms of comfort and user acceptance. For the physical construction of the prototype, CAD (Computer-Aided Design) software was used to develop a suitable casing that allows for safe, effective, and organized storage of the electronic components. Additionally, the electronic modules were programmed, and the Bluetooth module was configured to enable wireless data transmission from a smartphone to the prototype, ensuring a stable and efficient information flow from the device.